Understanding food choices and eating practices of Brazilian and Spanish athletes in aesthetics and weight class sports - Claudia Ridel Juzwiak (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: This study aimed at understanding determinants of food choices and eating practices of aesthetics and weight class athletes from two countries. Methods: In this qualitative study, through recorded in-depth individual and focal group interviews, gymnasts (n = 16) and martial arts (n = 18) athletes from Brazil and Spain reported their eating practices. Transcripts were analyzed through the Content Analysis method. Results: The main determinants of athletes' eating practices were the quest for a specific body in line with each sports' discipline and cultural food aspects. The everyday eating practices respected the country of origin's food culture; however, some practices, especially aiming at weight loss were similar in both countries and related to the sports discipline. Female Brazilian aesthetics athletes were particularly worried about achieving a thinner body. Martial arts athletes from both countries reported adopting fast weight loss strategies presently or at some point in their sports trajectory. Internal and external pressure to lose weight was a constant factor, especially amongst Brazilians. Conclusions: There is a specific body culture in each sport discipline, which extends beyond country borders. The idealized bodies athletes seek are constructed socially according to their sports. This confers them an identity and promotes beliefs and meanings to foodways. The sports-related eating practices which superimposed national foodways were similar in both countries, suggesting a group identity process, and the existence of a "sports discipline's food culture". Understanding athletes' determinants of food choices and eating practices provide insights to address the gap between nutritional recommendations and eating practices.